Effect of dietary inclusion levels of locust (Zonocerous variegatus) meal on growth performance and carcass characteristics of grower rabbits - Aliyu, Z.I.; Abdu, S.B.; Gandi, B.R. (Nigerian Journal of Animal Science, 2023)
An experiment was conducted to evaluate the effect of feeding inclusion levels of locust meal on growth performance and carcass characteristics of grower rabbits, with four dietary inclusion levels of locust meal (LM) at 0, 5, 10 and 15% respectively. Twenty eight (28) weaned rabbits aged 6 weeks of different breeds and sex were used for the study and randomly assigned to four dietary treatment groups with seven (7) rabbits per treatment in a completely randomized design (CRD). Parameters measured include: initial and final weights, weight gain, feed intake and feed conversion ratio, respectively. The trial lasted for eight (8) weeks. Data generated were set for analysis of variance (ANOVA) using SAS (2005) software package. The average daily weight gain (ADWG g/d) of rabbits fed the control diet, 5 and 15% LM were within the same level but higher (P<0.05) than those fed 10% level of inclusion. Average daily feed intake of rabbits fed 5% level of inclusion was higher (P<0.05) than those fed the control diet. However, the feed conversion ratio of rabbits fed the control diet, 5 and 15% levels of inclusion of LM was similar (5.39) but lower than those fed 10% LM (6.40). Rabbits fed 10% and 15% levels of inclusion of LM had higher (P<0.05) dressing percentage and carcass weight respectively, than those fed the control diet. In conclusion, dietary replacement of Soya bean meal with 5% locust meal improved growth performance and carcass characteristics.